TECHNOLOGIES OF CREATIVE THINKING OF STUDENTS IN THE PROFESSIONAL DEVELOPMENT SYSTEM AND DIRECTION TO INNOVATIVE PROFESSIONAL ACTIVITY (Western European Journal of Modern Experiments and Scientific Methods, 2025)
This paper presents cutting-edge technologies for developing creative thinking among trainees in professional development programs and steering them toward innovative occupational practices using artificial intelligence (AI)